The german minority in Romania. The past and the present = Mniejszość niemiecka w Rumunii. Przeszłość i teraźniejszość - Koźbiał, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Germans of Romania are not a single group, this is only purely geographical notion. They are independent groups: Transylvanian Saxons, Satu Mare Swabians, Banat Swabians, Landler, Zipser, Bukovina Germans, Bessarabia Germans and Dobruja Germans. The largest and oldest group is Transylvanian Saxons.
Keywords: Germans in Romania; German minority; Romania; Transylwania; German settlement; Niemcy w Rumunii; mniejszość niemiecka; Rumunia; osadnictwo niemieckie